Potassium and Humic Acid Synergistically Increase Salt Tolerance and Nutrient Uptake in Contrasting Wheat Genotypes through Ionic Homeostasis and Activation of Antioxidant Enzymes - Ghulam Abbas; Sadia Rehman; Manzer H. Siddiqui; Hayssam M. Ali; Muhammad Ansar Farooq; Yinglong Chen (Plants, 2022)
Salinity limits the growth and nutrient uptake in crop species. Studies show that both potassium (K) and humic acid (HA) improved plant tolerance to salinity. However, the interactive effect of K and HA on plant tolerance to salinity stress remains unknown. This pot study examined the effect of application of K (0, 5 or 10 mM) and HA (0 or 2 g kg−1), alone or in combination, on the growth and physiology under salinity (100 mM NaCl) in two wheat genotypes (SARC 1, salt tolerant; and SARC 5, salt sensitive). The results revealed that salt stress reduced shoot biomass by 35% and 49% in SARC 1 and SARC 5, respectively. Salinity induced overproduction of H2O2 and lipid peroxidation in both genotypes, but the decline in pigments and stomatal conductance was more profound in SARC 5 than in SARC 1. Combined application of 10 mM K and HA was most effective in alleviating salt stress with improved plant biomass by 47% and 43% in SARC 1 and SARC 5, respectively. Combined application of 10 mM K and HA mitigated salt and induced oxidative stress with the activities of APX, CAT, POD and SOD increased by up to 2.8 folds in SARC 1, and by upto 2.5 folds in SARC 5, respectively. Root and shoot Na contents were increased, while K, Fe and Zn contents were decreased under saline conditions. HA combined with K decreased Na and increased K, Fe and Zn contents in both genotypes. Combined application of 10 mM K and HA was more promising for increasing wheat salt tolerance and nutrient uptake and genotype SARC 1 performed better than SARC 5 for cultivation on saline soils.